B‐type natriuretic peptide trend predicts clinical significance of worsening renal function in acute heart failure. (25th November 2019) - Wettersten, Nicholas; Horiuchi, Yu; van Veldhuisen, Dirk J.; Mueller, Christian; Filippatos, Gerasimos; Nowak, Richard; Hogan, Christopher; Kontos, Michael C.; Cannon, Chad M.; Müeller, Gerhard A.; Birkhahn, Robert; Taub, Pam; et al.
Abstract: Aims: In acute heart failure (AHF), relationships between changes in B‐type natriuretic peptide (BNP) and worsening renal function (WRF) and its prognostic implications have not been fully determined. We investigated the relationship between WRF and a decrease in BNP with in‐hospital and 1‐year mortality in AHF. Methods and results: The Acute Kidney Injury NGAL Evaluation of Symptomatic heart faIlure Study (AKINESIS) was a prospective, international, multicentre study of AHF patients. Severe WRF (sWRF) was a sustained increase of ≥44.2 μmol/L (0.5 mg/dL) or ≥50% in creatinine, non‐severe WRF (nsWRF) was a non‐sustained increase of ≥26.5 μmol/L (0.3 mg/dL) or ≥50% in creatinine, and WRF with clinical deterioration was nsWRF with renal replacement therapy, inotrope use, or mechanical ventilation. Decreased BNP was defined as a ≥30% reduction in the last measured BNP compared to admission BNP. Among 814 patients, the incidence of WRF was not different between patients with or without decreased BNP (nsWRF: 33% vs. 31%, P = 0.549; sWRF: 11% vs. 9%, P = 0.551; WRF with clinical deterioration: 8% vs. 10%, P = 0.425). Decreased BNP was associated with better in‐hospital and 1‐year mortality regardless of WRF, while WRF was associated with worse outcomes only in patients without decreased BNP. In multivariate Cox regression analysis, decreased BNP, sWRF, and WRF with clinical deterioration were significantly associated with 1‐year mortality. Conclusions: Decreased BNP was associated with better in‐hospital and long‐term outcomes. WRF was only associated with adverse outcomes in patients without decreased BNP.